Asparagus racemosus silver chloride nanoparticles and Kaempferia rotunda mediated silver/silver chloride nanoparticles inhibit human hepatocellular and lung cancer cell lines - Syed Rashel Kabir; Mohammad Taufiq Alam; Md Belal Uddin (Biochemistry and Biophysics Reports)
Recently, we have reported that biogenic silver/silver chloride nanoparticles from Asparagus racemosus (A. racemosus-AgCl-NPs) and Kaempferia rotunda (K. rotunda-Ag/AgCl-NPs) inhibited different cancer cells by inducing apoptosis and several genes alteration. Here for the first time, we assessed the effects of these two nanoparticles on human lung (A549) and hepatocellular (SMMC-7721) carcinoma cell lines. A. racemosus-AgCl-NPs and K. rotunda-Ag/AgCl-NPs inhibited A549 cell growth with IC50 values of 22.7 and 59.7 μg/ml and the calculated IC50 values for SMMC-7721 cell were 89.3 and 126.3 μg/ml, respectively. A. racemosus-AgCl-NPs exerted higher cytotoxicity against HEK293T cells than doxorubicin and K. rotunda-Ag/AgCl-NPs. Both the nanoparticles induced apoptosis in A549 and SMMC-7721 cell lines. A significant rise of early apoptotic cells and late apoptotic cells was found for A549 cells after treatment with A. racemosus-AgCl-NPs and stained with FITC-annexin V/PI. Apoptosis in A549 cells was further confirmed by monitoring the alteration of the expression level of several genes using real-time PCR and cell cycle arrest by flowcytometry after treatment with A. racemosus-AgCl-NPs. The expression of STAT-3, TNFα, and EGFR genes was decreased with the increase of caspase-8, FAS, and FADD gene expression. G2/M cell cycle phase was arrested after treatment of A549 cells with A. racemosus-AgCl-NPs.